The New Age of Artificial Intelligence Regards Bharat and World Affairs - Chamoli, Amit (Future Science, 2023)
There is a flood of modern machines in the world, whose form has been taken by AI, it is entering the life of every person, whether it is your TV or fridge, it is visible in every field, from automobile to mobiles phone. Everyone has become accustomed to AI. The special thing is that in this era of modernity, the help of AI is being taken to increase the yield of agriculture. Farmers are able to spray their crops through drones. So in the same world, AI is also being used in large quantities in the fields of war like drone missile, guided missile, satellite missile etc. This AI is moving towards the new future of the world by which either peace will be established in the future or a devastating war will be fought. Although AI is likely to be operated by humans only because if this does not happen then the future of the world will be in the hands of AI. But given the various AI stages, this can only be imagined The Russia-Ukraine war is now at a more disastrous stage, in such a situation, what role AI can play in the search for peace remains to be seen. Due to differences with you and hunger for expansion, today the world is once again at a disastrous stage, among them China - Taiwan, Isreal-Iran etc. countries are standing on the front-line regarding the war against each other. Which cannot be seen normally. The related research paper attracts more attention to this and also questions the utility of AI. Although it will prove useful in some areas, can Ai be used for peace instead of war? it remains to be known